Absorption Coefficients of Phenolic Structures in Different Solvents Routinely Used for Experiments - Julia A. H. Kaeswurm; Andreas Scharinger; Jan Teipel; Maria Buchweitz (Molecules, 2021)
Phenolic structures are of great interest due to their antioxidant properties and various postulated benefits on human health. However, the quantification of these structures in fruits and vegetables, as well as in vivo or in vitro experiments, is demanding, as relevant concentrations are often low, causing problems in exactly weighing the respective amounts. Nevertheless, the determination of used concentrations is often a prerequisite for accurate results. A possibility to quantify polyphenol is the use of UV/vis spectroscopy. Therefore, the absorption coefficients of selected phenolic structures were determined in three different solvents relevant for polyphenol research (water/methanol (50/50, v/v), water, and phosphate buffer at pH 7.5). To confirm the values based on weight and to avoid errors due to impurities, hygroscopic effects, and inadequate balance care, the mass concentrations were additionally determined by quantitative NMR (q-NMR). The coefficients presented in this article can help to quickly and easily determine accurate concentrations in a laboratory routine without wasting the often-precious standard compounds.